Pronominal Subject Expression in Spoken Modern Hebrew: A Diachronic Perspective - Shor, Leon (Journal of Semitic studies, 2022)
As a consequence of the sociolinguistic circumstances of its emergence, the morpho-syntactic profile of Modern Hebrew (MH) originates in several sources - classical layers of Hebrew, pre-existing written practices, contact-induced influence of the native languages of the early MH speakers and internal linguistic developments. Adopting a diachronic corpus-based perspective, the present study focuses on one morpho-syntactic feature, the distribution of first and second person free subject pronouns with suffix (qaṭal) and prefix ( yiqṭol) conjugation verbs. In contrast to the mainly synchronic studies of that feature in MH, the starting point of the present study is data extracted from historical recordings documenting the spontaneous speech of four generations of MH speakers over more than 50 years. Our data indicate two opposite trends: On the one hand, there is a relative stability in the rates of free pronoun usage from the 1960s until the 2010s in two aspects: the near obligatory presence of the free 1SG pronoun ani in the prefix-conjugation, and the relatively low rates of free pronouns in the remaining persons. On the other hand, a significant decrease in the use of the 1SG pronoun ani in the suffix-conjugation was found throughout the years.1